Effects of regulatory focus and processing styles on perceiving group facial emotion: a mediation study - Lee, Xin Hui (2017)
Research in the area of facial emotion perception had produced mixed findings as to which processing style led to better recognition performance. Such mixed findings presented a research gap, in which my study intends to reconcile by exploring whether regulatory focus mediates the effect of processing styles on perception of group facial emotion. Specifically, a match between promotion-focus and global processing, as well as between prevention-focus and local processing was proposed. This constituted a regulatory fit condition. Furthermore, since perceiving group facial emotion is more appropriate to reflect the reality of societal and organizational context, my study seeks to extend previous findings of processing styles towards perceiving more than a single face. Processing styles and regulatory focus were primed using Navon task and implicit poster priming respectively, prior to engaging in group facial emotion recognition task. Results did not find evidence for the hypothesized mediation effect. Participants in the regulatory fit condition did not show enhanced performance as compared to those in the regulatory mis-fit condition. However, side analysis found significance for processing styles as a predictor for the performance levels (reaction time) of group facial emotion recognition, as well as the main effect of regulatory focus on accuracy of recognition. Limitations and implications of the study were discussed in the paper.